Efficacy of Flecainide in Catecholaminergic Polymorphic Ventricular Tachycardia Is Mutation-Independent but Reduced by Calcium Overload - Hwang, Hyun Seok; Baldo, Marcelo P.; Rodriguez, Jose Pindado; Faggioni, Michela; Knollmann, Bjorn C. (Frontiers in Physiology, 2019)
Background: The dual Na+ and cardia Ca2+-release channel inhibitor Flecainide (FLEC) is effective in patients with catecholaminergic polymorphic ventricular tachycardia (CPVT), a disease caused by mutations in cardiac Ca2+-release channels (RyR2), calsequestrin (Casq2) or calmodulin. FLEC suppresses spontaneous Ca2+ waves in Casq2-knockout (KO) myocytes, a CPVT model. However, a report failed to find FLEC efficacy against Ca2+ waves in another CPVT model, RyR2-R4496C heterozygous mice, raising the possibility that FLEC efficacy may be mutation dependent. Objective: To address this controversy, we compared FLEC in Casq2-KO and RyR2-R4496C myocytes and mice under identical conditions. Methods: After 30min exposure to FLEC (6μM) or vehicle (VEH), spontaneous Ca2+ waves were quantified during a 40s pause after 1Hz pacing train in the presence of isoproterenol (ISO, 1μM). FLEC efficacy was also tested in vivo using a low dose (LOW: 3mg/kg ISO + 60mg/kg caffeine) or a high dose catecholamine challenge (HIGH: 3mg/kg ISO + 120mg/kg caffeine). Results: In myocytes, FLEC efficacy was strongly dependent on extracellular [Ca2+]. At 2mM Ca2+, only Casq2-KO myocytes exhibited Ca2+ waves, which were strongly suppressed by FLEC. At 3mM Ca2+, both groups had similar frequent Ca2+ waves. The efficacy of FLEC had reduced in Casq2-KO myocytes but was not effective in RyR2-R4496C myocytes. Analogous to the results in myocytes, RyR2-R4496C mice (n=12) had significantly lower arrhythmia scores than Casq2 KO mice (N=9), but the pattern of FLEC efficacy was similar in both groups (i.e., reduced FLEC efficacy after high dose catecholamine challenge). Conclusion: FLEC inhibits Ca2+ waves in RyR2-R4496C myocytes, indicating that RyR2 channel block by FLEC is not mutation-specific. However, FLEC efficacy in myocytes and in vivo is reduced by Ca2+ overload (extracellular [Ca2+] or Caffeine-induced), which could explain conflicting literature reports.